Outdoor furniture - Engler, Nick (Emmaus, Pa. : Rodale Press, 1988)
Each project plan includes an exploded view, detailed drawings and photographs, complete materials list, step-by-step insturctions, time-saving tips, and easy-to-follow explanations of important woodworking techniques
Illustrations on lining papers
Keywords: Outdoor furniture -- Design and construction